Diagnosis of Black Queen Cell Virus, Deformed Wing Virus and Acute Bee Paralysis Virus in symptomatic African honey bees (Apis mellifera scutellata) of Costa Rica using RT-PCR in real time. - Chaves Guevara, Guisella (2016)
After beekeeper claims of bee diseases in beehives located in the South central region of the province of San José, Costa Rica, samples were collected from live adult Apis mellifera scutellata bees having presumptive symptoms of viral infection. Samples were extracted and processed in the laboratory. This is the first diagnostic in Costa Rica of the presence of the Black Queen Cell Virus (BQCV) and the Acute Bee Paralysis Virus (ABPV) in the province of San José in the canton of Turrubares, the district of San Pedro and the canton of Tarrazú, the district of San Marcos, respectively. Furthermore, this is also the second time that the Deformed Wing Virus DWV was detected in diseased bees in the country, in this occasion using PCR. Information about viral diseases in our country is still scarce; therefore, the implementation of these methods opens the possibility to offer beekeepers a rapid, specific and sensitive diagnosis. The development of these techniques could also be the starting point for conducting research to determine the prevalence of these viruses in beehives as well as potential risk factors associated with these infections.